Florida Predatory Stink Bug (unofficial common name), Euthyrhynchus floridanus (Linnaeus) (Insecta: Hemiptera: Pentatomidae) - Frank W. Mead; David B. Richman (EDIS)
The predatory stink bug, Euthyrhynchus floridanus (Linnaeus), is considered a beneficial insect because most of its prey consists of plant-damaging bugs, beetles, and caterpillars. This stink bug is primarily a Neotropical species that ranges into southeastern quarter of the United States. It seldom plays more than a minor role in the natural control of insects in Florida, but its prey includes such economic species as southern green stink bug, Nezara viridula (Linnaeus); orangedog, Papilio cresphontes Cramer; velvetbean caterpillar, Anticarsia gemmatalis Hübner; Colorado potato beetle, Leptinotarsa decemlineata (Say); West Indian sugarcane rootstalk borer, Diaprepes abbreviatus (Linnaeus), and others. This document is EENY-157 (originally published as DPI Entomology Circulars 174 and 242), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000.